(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides information on the role of modern pedagogical technologies in the teaching of engineering graphics, the achievements and shortcomings of the use of modern pedagogical technologies, and recommendations aimed at improving the quality of education with their help.